FeLV-induced feline leukemia as a natural model for leukemia pathophysiology study (review) - T. V. Tabakaeva; A. V. Tsybulsky; K. A. Baranchugova; I. V. Galkina; M. Yu. Shchelkanov (Ветеринария сегодня)
Leukemia is alarge group of diseases different in etiopathogenetic mechanisms and common in almost all mammalian species. There view focuses on feline leukemia, a common disease of domestic and wild felids (Carnivora, Felidae), being one of the main causes of their deaths. Feline leukemia pathogenesis and etiology are described; possible methods for the infection treatment and prevention, as well as possibility of using cats as a model for feline leukemia study areassessed. Feline leukemia etiological agent is a feline leukemia virus (FeLV), having single-stranded RNA genomesurrounded with icosahedral capsidformedbyp27 capsid protein monomers. Leukemia clinical man ifestations in felids depend on high virulence of the virus and the disease is characterized with pronounced clinical picture and multipleorgan dysfunction. Treatment of leukemia in cats is ineffective and is mainly aimedat maintaining the functions of the body organs and systems. Immunomodulators and chemotherapy are alsoused. Vaccination isusedas apreventive measure, but commercially available adjuvanted and non-adjuvanted vaccinesdo not confer effective protection from the infection. The leukemia virus is reportedin wildfelids includingrare and endangeredfeline species that is undoubtedly affects their population sizes. Despite veryfew data on leukemia, the reported cases show that leukemia in large cats is also severe and fatal. Feline leukemia, despite the accumulated of data, remainsan on going serious and unresolved problem not only for veterinarians, but also for ecologists, zoologists and virologists involvedin the research related to the feline family, study of retroviruses and biodiversity conservation on the planet. Furthe rapplied and fund a mental research and verification there of in the field of feline leukemia virus study, leukemia treatment and prevention are required.